2020
DOI: 10.1007/jhep09(2020)088
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the gauge and scalar sectors of the doublet left-right symmetric model

Abstract: We consider a left-right symmetric extension of the Standard Model where the spontaneous breakdown of the left-right symmetry is triggered by doublets. The electroweak ρ parameter is protected from large corrections in this Doublet Left-Right Model (DLRM), contrary to the triplet case. This allows in principle for more diverse patterns of symmetry breaking. We consider several constraints on the gauge and scalar sectors of DLRM: the unitarity of scattering processes involving gauge bosons with longitudinal pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 100 publications
0
9
2
Order By: Relevance
“…The high-energy analogue, the so-called Keung-Senjanović process [15], is a promising probe of the same source of lepton number violation at the LHC or future colliders. In addition, the presence of right-handed charged currents mediated by W R exchange and of heavy scalar bosons with flavor-changing interactions lead to a rich flavor phenomenology, with new contributions to a broad range of processes including CP violation in meson mixing and decays [16][17][18][19][20][21][22], nuclear β-decay [23,24], electroweak precision observables [25][26][27], and electric dipole moments (EDMs) of leptons, nucleons, nuclei, atoms, and molecules [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-energy analogue, the so-called Keung-Senjanović process [15], is a promising probe of the same source of lepton number violation at the LHC or future colliders. In addition, the presence of right-handed charged currents mediated by W R exchange and of heavy scalar bosons with flavor-changing interactions lead to a rich flavor phenomenology, with new contributions to a broad range of processes including CP violation in meson mixing and decays [16][17][18][19][20][21][22], nuclear β-decay [23,24], electroweak precision observables [25][26][27], and electric dipole moments (EDMs) of leptons, nucleons, nuclei, atoms, and molecules [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…These relations assume that the 27L,R × 1R,L parts of the LL and RR operators provide negligible contributions to the (ππ)I=0|Oi|K 0 matrix elements. These contributions can be obtained by using the LEC of the 27L,R × 1R,L representations, A(27,1) , discussed in section 5.2. Such an estimate shows that the dominant contributions to M1,2 indeed arise from the 8L,R × 1R,L parts of the operators.…”
mentioning
confidence: 99%
“…Conventionally, the very first proposals and studies of LRSM [1][2][3][4][5] considered a scalar bidoublet for generating fermion masses and also for electroweak symmetry breaking whereas a pair of scalar doublets were introduced for the purpose of left-right symmetry breaking at high energy scale. A very recent detailed study of this model can be found in [22]. On the other hand, the LRSM proposals put forward later [7][8][9][10][11][12] received much more attention due to the possibility of seesaw origin of light neutrino masses through a combination of type I seesaw [23][24][25][26] and type II seesaw [8,[27][28][29][30] or type III seesaw [31].…”
Section: Introductionmentioning
confidence: 99%
“…The gauge structure of the model prevents any renormalisable Yukawa couplings involving the scalar doublets χ L,R . The scalar potential V scalar is given by [22] V…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation